Factors Influencing Treatment Outcomes in Pulmonary Tuberculosis in Sanpatong Hospital,Chiang Mai Province - อักษร, พรวิไล (Disease Control Journal, 2007)
The objectives of this study were to assess treatment outcomes and determine the factors that influencing treatment outcomes in smear-positive pulmonary tuberculosis at Sanpatong hospital, Chiang Mai Province. All smear-positive pulmonary tuberculosis patients registered at Sanpatong hospital from 1 October 2001 to 30 September 2006 with known their outcomes were included and their medical record were retrospectively reviewed. Among 355 patients, treatment outcomes were classified as cured or completed in 68.2%, failured 1.4%, defaulted 3.9%,and died 22.5%. Of total 80 died with HIV 45% (36/80).The co-existing disease were found in 50.4%,icluding 38.7% with HIV. Sputum culture for Mycobacterial tuberculosis were performed in 109 cases (30.7%) and 79 of these (72.5%) were positive cultured .The rate of drug resistance was 13.9% (11/79) of culture proven tuberculosis. Factors that significantly asso ciated with death were HIV co-infection (OR 5.33, 95%CI 2.63-10.78) and cirrhosis (OR 109.2, 95%CI 11.1-1069.8). Factors that significantly associated with failured treatment were the previous history of TB treatment (OR 32.0,95%CI 2.52-405.0).There were no factors that significantly associated with defaulted treatment. In conclusion, the main factors that influencing pulmonary tuberculosis treatment outcomes in Sanpatong hospital were HIV co-infection, cirrhosis and the previous history of TB treatment, indicating that sputum culture for tuberculosis should be performed in all high risk groups and the necessity of collaboration between tuberculosis and HIV/AIDS control programmes.